Modelling time and frequency connectedness among energy, agricultural raw materials and food markets - Adebowale Musefiu Adeleke; Olabanji Benjamin Awodumi (Journal of Applied Economics, 2022)
The study analyzes volatility connectedness of energy, agricultural raw materials and food markets for both time and frequency domains (January 1960 to August 2020). The DY and BK approaches are adopted at both commodity-group and sub-group levels. Time domain estimates indicate that the energy market produced more risk spillover in the food market than raw material market. Rubber contributes the largest to spillover in the crude oil and sugar markets. Estimates from frequency domain reveal that raw material and food markets are net transmitter and net recipient of volatility spillover, respectively, at the lowest and highest frequency domains. Crude oil is the largest source of spillover in the tobacco, meat and natural gas markets in the high-frequency band. Finally, the meat and crude oil markets are the largest receiver of shock spillover from all other markets over the low- and high-frequency bands, respectively. Policy implications are derived from the findings.
Keywords: 330; agricultural raw materials; Energy; food; spillover index; time and frequency connectedness